Reliability and risk classification agreement of digital HYPOGLYRISK: implications for standardized medication safety services - Made Krisna Adi Jaya; Zullies Ikawati; Fita Rahmawati; Nanang Munif Yasin (Pharmaciana, 2026)
Hypoglycemia caused by medications is still a major safety issue for people with type 2 diabetes who are in an ambulatory therapy. To support pharmacists lead interventions, structured risk stratification is needed. The Medication-Related Hypoglycemia Risk Score Assessment Tool (HYPOGLYRISK) has been subjected to psychometric validation and digital development. However, its reproducibility among practitioners is crucial prior to broader implementation. This study assessed the inter-rater reliability and risk classification concordance of the digital HYPOGLYRISK instrument among practicing pharmacists. A methodological reliability and agreement study was performed with 46 licensed pharmacists who independently evaluated three standardized simulated patient cases categorized as low, moderate, and high risk using a digital platform. We used the intraclass correlation coefficient to look at the inter-rater reliability of total scores and the descriptive method to look at categorical agreement. The reliability test showed almost perfect agreement, with an intraclass correlation coefficient of 0.995 (95% confidence interval: 0.988-0.999). There was no difference in how the raters classified the risk categories for any case. There was perfect agreement for the clinical risk factor part, but there was a small difference in numbers for the behavioral medication safety part in the moderate-risk case, which involved 8.7% of raters. This did not change the final risk categorization. There was no misclassification between extreme risk categories. These results show that the digital HYPOGLYRISK tool gives very consistent scores and stable risk stratification across pharmacists. This finding supports its use as a standardized tool for pharmacist-led medication safety services in ambulatory diabetes care.